(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Inclusive education aims to provide equal learning opportunities for all students, regardless of their physical, cognitive, linguistic, or socio-economic backgrounds. In this context, teaching foreign languages in inclusive classrooms requires a multidisciplinary approach that integrates pedagogical, psychological, and linguistic strategies. This article explores the theoretical foundations of foreign language teaching in inclusive settings and analyzes effective methods for practical implementation. Drawing on international research and case studies, the paper offers a framework for developing adaptive, engaging, and effective language instruction that accommodates diverse learners.